Performing an FSC audit. Issue 3 (9th June 2021) - Cook, William; Turnhout, Esther; van Bommel, Séverine
Abstract : Purpose: The Forest Stewardship Council (FSC) intends to promote responsible forestry through its certification scheme. The primary engine that drives this promotion is auditing. Audits serve a dual purpose: they make forest managers accountable for their claim of meeting the FSC standard, and they make the actions of auditors and auditee account-able, or able to be put into an account. The latter of these is rarely investigated, despite it being crucial to understanding how FSC audits are done. Design/methodology/approach: This article examines FSC forest certification audits as practices where the FSC standards gain meaning. In-depth analysis of these practices enables insight into how different values related to forest certification and auditing are articulated and negotiated in practice, characterizing particular modes of auditing. In this paper, the authors examine the practices of FSC forest management auditors in multi-day audits in Africa and in Spain. Their materials were analyzed and coded using Goffman's elements of dramaturgy. Findings: The authors' findings show that auditing practices entail a series of nested performances in which the auditors and auditees interact together and in which front stage and back stage performances constantly alternate as auditors and auditees perform for each other and simultaneously for an absent audience. Originality/value: The authors' analysis demonstrates how in these performances, professional values related to following auditing rules and ensuring that audits are rendered account-able in a particular way take a prominent position. This risks overshadowing the accountability of the FSC system which is ultimately grounded in its ambition to improve forest conservation and management.